Colloid osmotic pressure of contemporary and novel transfusion products - Klanderman, Robert B. (Vox Sang, 2020)
BACKGROUND AND OBJECTIVES: Colloid osmotic pressure (COP) is a principal determinant of intravascular fluid homeostasis and a pillar of fluid therapy and transfusion. Transfusion‐associated circulatory overload (TACO) is a leading complication of transfusion, and COP could be responsible for recruiting additional fluid. Study objective was to measure COP of blood products as well as investigate the effects of product concentration and storage lesion on COP. MATERIALS AND METHODS: Three units of each product were sampled longitudinally. COP was measured directly as well as the determinants thereof albumin and total protein. Conventional blood products, that is red blood cell (RBC), fresh‐frozen plasma (FFP) and platelet concentrates (PLTs), were compared with their concentrated counterparts: volume‐reduced RBCs, hyperconcentrated PLTs, and fully and partially reconstituted lyophilized plasma (prLP). Fresh and maximally stored products were measured to determine changes in protein and COP. We calculated potential volume load (PVL) to estimate volume recruited using albumin's water binding per product. RESULTS: Colloid osmotic pressure varies widely between conventional products (RBCs, 1·9; PLTs, 7·5; and FFP, 20·1 mmHg); however, all are hypooncotic compared with human plasma COP (25·4 mmHg). Storage lesion did not increase COP. Concentrating RBCs and PLTs did not increase COP; only prLP showed a supraphysiological COP of 47·3 mm Hg. The PVL of concentrated products was lower than conventional products. CONCLUSION: Colloid osmotic pressure of conventional products was low. Therefore, third‐space fluid recruitment is an unlikely mechanism in TACO. Concentrated products had a lower calculated fluid load and may prevent TACO. Finally, storage did not significantly increase oncotic pressure of blood products.